The effects of iron oxide incorporation on the chondrogenic potential of three human cell types. (7th March 2012) - Saha, Sushmita; Yang, Xuebin B.; Tanner, Steven; Curran, Stephen; Wood, David; Kirkham, Jennifer
Abstract Non‐invasive monitoring of living cells in vivo provides an important tool in the development of cell‐based therapies in cartilage tissue engineering. High‐resolution magnetic resonance imaging (MRI) has been used to monitor target cell populations in vivo. However, the side‐effects on cell function of the labelling reagents, such as superparamagnetic iron oxide (SPIO), are still unclear. This study investigated the effect of SPIO particles on the chondrogenic differentiation of human bone marrow stromal cells (HBMSCs), neonatal and adult chondrocytes in vitro. Cells were labelled with SPIO for 24 h and chondrogenesis induced in serum‐free medium including TGFβ3. For labelled/unlabelled cells, viability, morphology and proliferation were determined using CellTracker™ Green and PicoGreen dsDNA assays. The expression of SOX9, COL2A1 and ACAN was investigated using qRT–PCR after 2, 7 and 14 days. The results showed that viability was unaffected in all of the cells but cell morphology changed towards a 'stretched' phenotype following SPIO uptake. Cell proliferation was reduced only for labelled neonatal chondrocytes. SOX9 and COL2A1 expression decreased at day 2 but not at days 7 and 14 for labelled HBMSCs and adult chondrocytes; ACAN expression was unaffected. In contrast, SOX9 and COL2A1 expression were unaffected in labelled neonatal chondrocytes but a decrease in ACAN expression was seen at day 14. The results suggest that downregulation of chondrogenic genes associated with SPIO labelling is temporary and target cell‐dependent. Resovist® can be used to label HBMSCs or mature chondrocytes for MR imaging of cells for cartilage tissue engineering. Copyright © 2012 John Wiley & Sons, Ltd.